The Perceptions Held By South Asian American Youth When Faced With Ethnic Homophily Practices in Voting: A Mixed Method Analysis - Sebastian, Aaron (Journal of Student Research, 2024)
This study explores the phenomenon of ethnic homophily in the context of voting behavior, or the practice of voting for, or having a preference towards, candidates of a similar ethnic background. Situated within the United States, South Asian American youth ages 18-27 are analyzed under this study, and a number of different factors are analyzed. Ultimately, the extent to which ethnic homophily impacts a voter’s behavior, the limitations to its presence, and the contexts in which it is emphasized are all explored within this study. A mixed-methods analysis was utilized with correlation coefficients, and a superarching thematic analysis, being conducted. Ethnic homophily, as the study results qualify, often impacts individuals by exacerbating struggles with cultural identity, creating isolating voting experiences, and misconstruing the sentiments of feeling represented. The limitations of ethnic homophily within South Asian American voters was ultimately found to only exist as a secondary factor to political propositions of candidates, and the contexts in which it is emphasized are within familial pressures, conforming to cultural norms, and begetting cultural representation for legislative processes.